Uji Daya Terima Dan Analisis Protein Es Krim Dengan Penambahan Tepung Daun Kelor (Moringa Oleifera) - Syam, Marsuki; Fitri Wahyuni; Icha Dian Nurcahyani (UNIVERSITAS NGUDI WALUYO, 2021)
Moringa is a type of functional food that contains many nutrients both macro nutrients and micronutrients that have been widely used in combating malnutrition in children and efforts to improve the immune system in many developing countries. Ice cream is the most popular food in the world and is very popular by all circles of society because of its good taste, soft texture and high nutrient content and can be one of the media in nutritional improvement. To know the acceptability and analysis of the protein content of ice cream with the addition of moringa leaf flour. This type of research is experimental research with posttest design one shot group design that is done adding moringa leaf flour to the manufacture of ice cream with some concentration.Research shows that panelists' acceptability to color aspects, aroma, texture, and aspects of taste and weighting value, the best formulation of ice cream with the addition of moringa leaf flour is F1 compared to F2, F3, and F4, ie with a value of F1 52.86, F2 42.86, F3 42.01, F4 33.29, although when compared to F0 (ice cream krontrol) the value is lower ie , 54,65. The results of protein analysis Ice cream with the addition of moringa leaf flour increased from 3.3% to 4.1% this occurred after the addition of moringa leaf flour 5%. from the results of the study of acceptability to aspects of color, aroma, texture, and taste obtained the best formulation of ice cream with the addition of moringa leaf flour that is F1 compared to F2, F3, and F4, namely with a value of F1 52.86, F2 42.86, F3 42.01, F4 33.29, although when compared to F0 (ice cream control) the value is lower that is, 54.65. There is an increase in the protein content of ice cream with the addition of moringa leaf flour 10 g which is 0.0888 g, compared to without the addition of moringa leaf flour or 0 g of 0.0686g. ABSTRAK Kelor merupakan jenis pangan fungsional yang mengandung banyak zat gizi baik zat gizi makro maupun zat gizi mikro yang telah banyak digunakan dalam memerangi kekurangan gizi pada anak-anak dan upaya untuk meningkatkan sistem kekebalan tubuh dibanyak negara berkembang. Es krim merupakan makanan yang paling populer di dunia dan sangat digemari oleh semua kalangan masyarakat dikarenakan rasanya yang enak, teksturnya yang lembut dan mengandung zat gizi yang tinggi dan dapat menjadi salah satu media dalam perbaikan gizi. Untuk mengetahui daya terima dan analisis kandungan protein es krim dengan penambahan tepung daun kelor. Jenis penelitian ini adalah penelitian eksperimental dengan desain posttest one shot group desain yakni dilakukan menambahkan tepung daun kelor pada pembuatan es krim dengan beberapa konsentrasi. Penelitian menunjukkan bahwa daya terima panelis terhadap aspek warna, aroma, tekstur, dan aspek rasa dan hasil pembobotan nilai, formulasi terbaik es krim dengan penambahan tepung daun kelor yaitu F1 dibandingkan dengan F2, F3, dan F4, yakni dengan nilai F1 52,86, F2 42,86, F3 42,01, F4 33,29, meskipun jika dibandingkan dengan F0 (es krim krontrol) nilainya lebih rendah yakni, 54,65. Hasil analisis protein Es krim dengan penambahan tepung daun kelor meningkat dari 3,3% menjadi 4,1% hal ini terjadi setelah penambahan tepung daun kelor 5%. dari hasil penelitian daya terima terhadap aspek warna, aroma, tekstur, dan rasa diperoleh hasil formulasi terbaik es krim dengan penambahan tepung daun kelor yaitu F1 dibandingkan dengan F2, F3, dan F4, yakni dengan nilai F1 52,86, F2 42,86, F3 42,01, F4 33,29, meskipun jika dibandingkan dengan F0 (es krim kontrol) nilainya lebih rendah yakni, 54,65. Terdapat peningkatan kandungan protein es krim dengan penambahan tepung daun kelor 10 g yaitu 0,0888 g, dibandingkan dengan tanpa penambahan tepung daun kelor atau 0 g yaitu 0,0686 g.